Pengaruh Bermain Flashcard Terhadap Kemampuan Mengenal Huruf Hijaiyah Anak Kelompok B di Raudhatul Athfal Almourky - Binti Asmawati; Sri Wahyuningsi Laiya; Nunung Suryana Jamin (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This research aims to determine whether flashcard play affects the ability to recognize Hijaiyah letters in Group B children at Raudhatul Athfal Almourky, Telaga District, Gorontalo Regency. The research used a quantitative experimental method (one group pretest-posttest design). Based on a sample of 20 children, the results improved from the pre-test to the post-test scores. The pre-test data had an average score of 17.4 and a standard deviation of 4.805, while the post-test data showed an average score of 35.4 and a standard deviation of 4.357. These results demonstrate a significant effect before and after the intervention. Based on the statistical test output, the significance test showed a t-count of 6.81, greater than the t-table of 2.093. Therefore, it can be concluded that H0 is rejected and H1 is accepted. Thus, the research hypothesis states that flashcard play has a significant effect on the ability to recognize Hijaiyah letters in Group B children at Raudhatul Athfal Almourky, Telaga District, Gorontalo Regency.